Develop and Engage Talents: A Preliminary Study at Islamic Banks in Northern Region of Malaysia - Mustafa Kamil, Bidayatul Akmal; Iqbal, Fatin Izzati (CSRC Publishing, 2017)
Purpose: Attract, select, develop and engage the right talents at the right time, place and position become essential for upgrading the management system in the banking sector. This study identifies the development of talents through talent management and succession planning, which may engage those employees with the banks. Design/Methodology/Approach: In this preliminary study, 180 copies of questionnaires were distributed to the bankers who are currently working with some Islamic Banks in the Northern region of Malaysia; Kedah, Perlis and Pulau Pinang. The simple random sampling techniques applied. The analysis of this study are all descriptive.Findings: This study explores the descriptive analysis on talent management, succession planning and talent engagement, that might be particularly focus on the mean of each variables. The analyses show that, the respondents believed that talent management and succession planning, as well as talent engagement should well-known exist and outstandingly being implemented in Islamic banking industry. Implications/Originality/Value: Islamic banks demand for talents of bankers that are not only well profound with Sharia knowledge but also capable to ascertain the differences between Islamic banking and finance regulation at par with conventional practices.The analyses of the data are expected to give practical contribution to the Islamic banks to have a better talent management mechanism and succession planning program for engaging their talents in the future.